CORRELATION HANDGRIP STRENGTH TO GINGIVAL RECESSION FROM BRUSHING TEETH TRAUMA: PRELIMINARY STUDY - Ferlita Shafri Djohan, Frita (Fakultas Kedokteran Gigi Unjani, 2025)
Brushing is affected by the strength of hand movements, including the grasping muscles. Excessive brushing of the teeth can result in trauma to the gingiva. This study aims to review the relationship between the strength of the grasping muscles and the occurrence of gingival recession. The cross sectional research method was carried out at Cirendeu State Elementary School, Cimahi. Measurements of handheld muscle strength were performed with a hand dynamometer and gingival recession on an intra-oral clinical examination. The results of the two data will be correlation tests to see the relationship using the Pearson Chi Square Test. The results of the study of twenty children in grade 6 elementary school were weak grip muscle strength of 30% in 6 male students and 20% moderate in 4 students, weak 20% in 4 female students, medium 15% in 3 female students, and strong 15% in 3 female students. There was a gingival recession of 10% each in 2 female and male students. The relationship between the occurrence of recession and strong grip muscle strength was 33.3% (p value <0.5). In 12-year-old children, there was no significant relationship between the strength of the grasping muscles and the occurrence of gingival recession. DOI : 10.54052/jhds.v4n3.p265-276